1999
DOI: 10.1210/jcem.84.4.5591
|View full text |Cite
|
Sign up to set email alerts
|

A Prospective Randomized Trial Comparing Low Dose Flutamide, Finasteride, Ketoconazole, and Cyproterone Acetate-Estrogen Regimens in the Treatment of Hirsutism

Abstract: Sixty-six hirsute women were randomized and treated with 1) flutamide (n = 15), 250 mg/day; 2) finasteride (n = 15), 5 mg/day; 3) ketoconazole (n = 16), 300 mg/day; and 4) ethinyl estradiol (EE)-cyproterone acetate (CPA; n = 20), 0.01 mg EE/day for the first week, 0.02 mg EE/day for the second week, and 0.01 mg EE/day for the third week, followed by a pause of 7 days, then 12.5 mg CPA/day added during the first 10 days of every month for 12 months. Hirsutism was evaluated by the Ferriman-Gallwey score, and hai… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

8
47
0
2

Year Published

2002
2002
2016
2016

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 112 publications
(57 citation statements)
references
References 33 publications
8
47
0
2
Order By: Relevance
“…49 Finasteride is approved by the FDA for the treatment of benign prostatic hyperplasia (BPH) and androgenic alopecia, and is known to have an excellent safety profile, [51][52][53] and has also been shown to have fewer side effects and drug interactions than ketoconazole. 54 Its most common adverse effect is decreased libido, and no laboratory workup is required except for monitoring of prostate-specific antigen in men with BPH who are using it long-term. In the only previous study of its use in CSC, finasteride was shown to improve CMT and SRF in five patients who were treated with it for 3 months and followed for 3 more, with no adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…49 Finasteride is approved by the FDA for the treatment of benign prostatic hyperplasia (BPH) and androgenic alopecia, and is known to have an excellent safety profile, [51][52][53] and has also been shown to have fewer side effects and drug interactions than ketoconazole. 54 Its most common adverse effect is decreased libido, and no laboratory workup is required except for monitoring of prostate-specific antigen in men with BPH who are using it long-term. In the only previous study of its use in CSC, finasteride was shown to improve CMT and SRF in five patients who were treated with it for 3 months and followed for 3 more, with no adverse events.…”
Section: Discussionmentioning
confidence: 99%
“…Differences in clinical efficacy of antiandrogen drugs are minor and the choice of drug depends on the availability, cost and its side-effects (7). A low-dose antiandrogen may be a suitable choice in an attempt to prevent the incidence of side-effects and complications (22,23).…”
Section: Discussionmentioning
confidence: 99%
“…Previously, successful results had been obtained with finasteride in woman with hirsutism (9,25,26). Venturoli et al (22) reported that Ferriman -Gallwey scores in 15 women with hirsutism were significantly decreased (44%) after 12 months of finasteride therapy. Falsetti et al (11) observed that finasteride caused a significant reduction in the hirsutism scores in PCOS and idiopathic hirsutism at the end of 12 months.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Today, various satisfactory therapeutic regimens exist for the treatment of hirsutism (6). Among these, flutamide (Flu) is commonly defined as a pure selective anti-androgen with a non-steroidal structure and with no progestogenic, glucocorticoid, androgenic, oestrogenic or anti-gonadotrophic action (7).…”
Section: Introductionmentioning
confidence: 99%